Sinonasal cancer in a worker exposed to chromium in an unusual industrial sector - Comiati, Vera; Scapellato, Maria Luisa; Alexandre, Enrico; Volo, Tiziana; Borsetto, Daniele; Carrieri, Mariella; Emanuelli, Enzo; Cazzador, Diego (La Medicina del Lavoro, 2017)
Background: Occupational exposure to chromium is carcinogenic for human respiratory system. Due to the low incidence of sinonasal malignancies, there is still a paucity of evidence to confirm that chromium(VI) exposure is a cause of nasal cancer. Objectives: To report on a sinonasal cancer (SNC) of rare occupational origin, increasing the awareness on epidemiological knowledge of occupational exposures to chromium compounds. Methods: We describe a case of a 64-year-old chrome plater who worked in the galvanic industry in the early 1970s. After a latency period of 39 years, he was diagnosed with sinonasal undifferentiated carcinoma (SNUC). A brief review of the literature was conducted. Results: A thorough occupational history revealed a 4-year-long occupational exposure to chromium(VI) during a magnesium cylinder plating process involved in computer production. The patient underwent endoscopic endonasal removal of the SNUC. He is alive with no evidence of disease at 40-month follow-up. Our literature review identified 8 papers concerning 40 cases of chrome-induced sinonasal tumors. The maximum relative risk of SNC developing in chromium-exposed workers was 15.4. Conclusions: When dealing with patients diagnosed with SNC, the possibility of an underlying occupational risk is worth further investigation. Because chromium exposure is rare, and the incidence of SNUC is low, any information emerging on clinical and exposure-related aspects of SNCs in chrome plating workers can contribute to adding evidence on the possible causal relationship between chromium and sinonasal malignancies.